Surgical Treatment for Spinal Tuberculosis without Elevation of Inflammatory Biomarkers at the Initial Visit Mimicking Spinal Metastasis. (26th August 2020) - Sakamoto, Takuya; Takahashi, Hiroshi; Saito, Junya; Matsuzawa, Yasuo; Aoki, Yasuchika; Nakajima, Arata; Sonobe, Masato; Akatsu, Yorikazu; Yamada, Manabu; Akiyama, Yuki; Iwai, Tatsunori; Yanagisawa, Keita; et al.
Abstract : Here, we report a case of spinal tuberculosis without elevation of C-reactive protein (CRP) at the initial visit mimicking spinal metastasis. A 70-year-old woman developed progressive paraplegia without a history of injury and came to our hospital for evaluation. Severe compression to the spinal cord with osteolytic destruction of the spinal vertebrae at T6-7 was observed without elevation of CRP. A T4-9 posterior decompression and fusion were performed. Although the pathology revealed no malignant tumor cells, a positron emission tomography-computed tomography (PET-CT) showed upregulation of the thyroid gland and aspiration cytology revealed a thyroid carcinoma. Thus, we diagnosed her with spinal metastases from thyroid carcinoma. Conservative treatment was chosen with the hope of a significant neurologic recovery; however, 9 months after the primary surgery, she returned to our hospital with reprogressive paraplegia. In addition to progression of osteolytic changes to the T5-7 vertebrae, a coin lesion on the right side of the lung and elevation of CRP were observed. Finally, we diagnosed her with spinal tuberculosis based on the results of a CT-guided needle culture. Two-stage surgeries (posterior and anterior) were performed in addition to administering antituberculosis medications. At the 1-year postoperative follow-up evaluation, both neurologic function and laboratory data were improved with T5-9 complete fusion. It is difficult to determine based on imaging findings alone whether osteolytic vertebrae represent spinal metastases or tuberculosis. Even though inflammatory biomarkers, such as CRP, were not elevated, we should consider the possibility of not only spinal metastases but also tuberculosis when planning surgery involving osteolytic vertebrae. In addition, the combination of neurological, imaging, and pathological findings is important for the diagnosis of spinal tuberculosis.